2014
DOI: 10.3758/s13415-014-0291-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of negative content on the processing of gender information: An event-related potential study

Abstract: Previous research on emotion in language has mainly concerned the impact of emotional information on several aspects of lexico-semantic analyses of single words. However, affective influences on morphosyntactic processing are less understood. In the present study, we focused on the impact of negative valence in the processing of gender agreement relations. Event-related potentials (ERPs) were recorded while participants read three-word phrases and performed a syntactic judgment task. Negative and neutral adjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 79 publications
2
17
0
Order By: Relevance
“…They observed that the amplitude of the AN increased for negative adjectives containing morphosyntactic violations, while it decreased for positive adjectives, in comparison with neutral ones. The results of the study by Hinojosa et al (2014) follow a similar line. On the other hand, P600 modulations have been reported when presenting happy and sad film clips preceding subject-verb agreement violations (Vissers et al, 2010; Verhees et al, 2015).…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…They observed that the amplitude of the AN increased for negative adjectives containing morphosyntactic violations, while it decreased for positive adjectives, in comparison with neutral ones. The results of the study by Hinojosa et al (2014) follow a similar line. On the other hand, P600 modulations have been reported when presenting happy and sad film clips preceding subject-verb agreement violations (Vissers et al, 2010; Verhees et al, 2015).…”
Section: Introductionsupporting
confidence: 62%
“…In view of Jiménez-Ortega et al (2014) and supraliminal studies with similar procedures (Martín-Loeches et al, 2012; Hinojosa et al, 2014), we expect that the syntactic processing of the sentence will be impacted by subliminal emotional words. The expected results are an increase in anterior negativity in response to morphosyntactic anomalies when the subliminal adjective is emotionally negative, as well as the absence of this component when the adjective is positive, as in Martín-Loeches et al (2012) using supraliminal presentations.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…More recently, Hinojosa et al (2014) have studied the processing of negative words with gender violations. They reported a decrease in the amplitude of the LAN component when the mismatching word was negative.…”
Section: Emotional Words In Their Context: the Time Course Of Emotionmentioning
confidence: 99%
“…Martín-Loeches et al (2012) found that negative in contrast to positive words caused greater amplitudes of a left anterior negativity (LAN) ERP when participants were detecting syntactic anomalies, which involved a deeper processing of negativity, and a negative bias. Moreover, Hinojosa et al (2014) have shown that negative valenced words caused shorter LAN amplitude than neutral words in detecting errors in a syntactic judgment task (gender agreement), which was interpreted in terms of processing priority for emotional words in contrast to neutral words. In addition, with a gender agreement task, Díaz-Lago, Fraga, and Acuña-Fariña (2015) showed a late positive (P600) ERP associated with word emotionality and grammaticality.…”
mentioning
confidence: 96%